Reinsurance and Performance of the Ceding Companies: The Nigerian Insurance Industry Experience - Aduloju, Sunday Adekunle; Ajemunigbohun, Sunday Stephen (Economics and Business, 2017)
This paper examines the relationship between ceding office gross premium income, underwriting profit and financial stability. The study made use of primary and secondary data. The primary data were obtained from 246 respondents selected from those companies through the use of structured questionnaire. The secondary data obtained from the 2014 and 2015 published financials of the selected ten companies were used to determine the Reinsurance Ceded Ratio (RCR), Return on Asset (ROA), Return on Equity (ROE) as well as the Ratio of Reinsurance Recoverables to Policyholders Surplus (RRPHS). A descriptive research design was employed. The sampling technique adopted was purposive in nature. The study population comprises 56 insurance companies in Nigeria. More so, data collected was analysed using correlation analytical method. The results of this study are quite in line with previous studies and show that reinsurance purchase increases significantly the insurers’ premium income. It is also shown that profitability of the firm is sensitive to change in reinsurance utilisation and has a positive relationship with it. It was established in the study that purchasing reinsurance reduces insurers’ insolvency risk by stabilizing loss experience and increasing capacity. Recommendations were made.